The self-reversal origin of the reversed remanent magnetization in the igneous rocks containing the oxidized Fe-Ti oxide solid solutions - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2011)
I study the magnetic and paleomagnetic characteristics of the Pleistocene to Quaternary basalts from the West Carpathian Mountains. I have revealed the existence of the so-called self-reversal remanent magnetization bearing disordered-antiferromagnetic Fe-Ti phases, with the Néel temperatures of either TN = 430−450 °C (the Ti-Mgh phases) or with TN = 460−470 °C (Hem-Ilm phases). I have suggested for the first time to name of these phases in this article. It is very important that these phases are the only sources of the reversed RM, of the self-reversal origin, probably of the chemical remanent magnetization (CRM) origin. The basalts of Southern Slovakia were differentiated to these of the magnetite and Ti-rich Ti-Mt bearing rocks with normal polarity of RM, and those with the presence of the self-reversal RM bearing disordered-antiferromagnetic Ti-Mgh phases of the TN = 430 to 450 °C, and those of the disordered-antiferromagnetic Hem-Ilm phases of the TN = 460 − 470 °C, both of only reversed RM of the self-reversal origin. I present the original model based on the principe that the magnetite, hematite and Ti-rich titanomagnetite bearing rocks, without any disordered-antiferromagnetic phases, carry only normal – positive RM. The self-reversal remanent magnetization bearing disorderedantiferromagnetic magnetic phases of Fe-Ti oxide solid solutions carry only reversed remanent magnetization in the rocks. This model has been involved to explain the reversed or normal RM of submarine igneous rocks published in the literature. We anticipate that in all continental or submarine reversally magnetized rocks the disordered-antiferromagnetic Fe-Ti phases would be revealed, either in their initial, complete developed stages, or as the remnants of these phases.